The Reformed Church and the New Perspectives of Christendom in the Late Middle Ages - Silva Rocha, Tereza Renata (Eikón / Imago, 2016)
This article discusses post-Reformation Latin Christianity and the measures taken by the Church through the canons of the Fourth Lateran Council (1215), which establishes not only a new way of dealing with sin, but also defines the Devil. In addition, we analyze the emergence, in this context, of the Friars Preachers, who are notable for the reformulation of the preaching and for their insertion in the cities. New doctrinal formulations and religious practices are established, giving prominence to the Devil's performance and ways of fighting it. The Dominican Order, in this sense, has a central role in the fight against evil. Preachers, confessors and inquisitors, the Dominicans must warn, teach, combat the demons and punish deviations.
Keywords: Reform of the Church; Dominican Orden; Devil; Heresy; Golden Legend